1997
DOI: 10.1063/1.474239
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence spectroscopy of atomic zinc in rare-gas solids. I

Abstract: Steady-state and time-resolved luminescence spectroscopy of atomic zinc isolated in thin film samples of the solid rare gases, prepared by the cocondensation of zinc vapor with argon, krypton, and xenon has been recorded at 6.3 K using synchrotron radiation. Pairs of emission bands result from photoexcitation of the singlet 4p 1 P 1 ←4s 1 S 0 resonance transition of atomic zinc, even in annealed samples. In Zn/Ar the pair of emission bands were observed in the uv at 218.9 and 238 nm and for Zn/Xe in the near-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(58 citation statements)
references
References 29 publications
3
53
2
Order By: Relevance
“…The threefold splitting observed for the absorption bands of these metal atoms in the solid rare gases Ar, Kr and Xe (M/RG) has been assigned to the dynamic Jahn-Teller effect [8,9] on the assumption that the ground state metal atom is isolated in a highly symmetrical site of the solid rare gases. Excitation spectra recorded in luminescence studies confirm the existence of the threefold splitting in the Mg/RG [10], Zn/RG [11] and Cd/RG [12] systems. While much fewer matrix studies have been done on metal atoms in solid neon [4], absorption spectra of the three metals of interest to this work have been recorded.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The threefold splitting observed for the absorption bands of these metal atoms in the solid rare gases Ar, Kr and Xe (M/RG) has been assigned to the dynamic Jahn-Teller effect [8,9] on the assumption that the ground state metal atom is isolated in a highly symmetrical site of the solid rare gases. Excitation spectra recorded in luminescence studies confirm the existence of the threefold splitting in the Mg/RG [10], Zn/RG [11] and Cd/RG [12] systems. While much fewer matrix studies have been done on metal atoms in solid neon [4], absorption spectra of the three metals of interest to this work have been recorded.…”
Section: Introductionmentioning
confidence: 71%
“…The Mg/Ne and Zn/Ne luminescence data reported in this study completes the rare gas series for matrix-isolated atomic Mg [10] and Zn [11], allowing a full comparison to be made with the Cd/RG solids previously analysed. The irregular shifting of the excitation features in M/Ne compared with the other members in the M/RG series, illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the optical layout of the HIGITI apparatus located at HASYLAB/DESY in Hamburg has been presented in our earlier work, 3 only a brief description will be given here. Synchrotron radiation optimized in the VUV spectral region was used as the excitation source.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, d → s transitions are observed to be narrow and unshifted from their gas phase positions, while p → s transitions are now well known to be broad, exhibiting large Stokes-shifted emission. More recently, our group at Maynooth has looked at the luminescence of matrix-isolated atomic Zn, 8 Cd, 9 and Hg 10 and observed that the emission is dominated by P → S transitions. To date, no work has appeared on the luminescence of atomic Mn whose absorption 11 is also dominated by P ← S transitions.…”
Section: Introductionmentioning
confidence: 99%